Research on Highly Dynamic Node BLE Mesh Routing Strategy based on Limited Flooding - WU Xihang; HUANG Zhuo; LUO Senlin; WANG Fengxiang (Guangtongxin yanjiu)
【Objective】Bluetooth Low Energy (BLE) is a low-power, low-cost wireless communication technology, and the development of BLE Mesh further enhances the network scalability and communication range. Fruitymesh stands as the only open-source routing-based BLE Mesh networking strategy at present. However, using Fruitymesh in highly dynamic node environments leads to issues such as interruptions in tree-shaped topology network transmission links due to frequent node entries and exits, resulting lower data transmission success rates. To address this problem, this paper utilizes the networking principles of Fruitymesh and proposes a limited flooding-based routing strategy suitable for highly dynamic node scenarios.【Methods】By modifying the clustering scoring mechanism, the network topology is refined from a tree-shaped structure to a partial mesh structure, enhancing the overall reliability of the network topology. Simultaneously, a route selection mechanism is introduced, and a limited flooding routing strategy is designed.【Results】Through simulation verification, compared to Fruitymesh, the limited flooding routing strategy demonstrates a 71.4% improvement in network topology robustness. In fixed-point attacks, the overall network Packet Delivery Rate (PDR) is increased from 15.00% to 85.67%. In random attacks, the overall network PDR is increased from 53.00% to 92.29%. And the average PDR of non-neighboring nodes in the limited flooding routing algorithm is improved from 78.73% to 86.97% as compared to the flooding routing algorithm.【Conclusion】The proposed limited flooding routing strategy in this paper effectively enhances the network topology robustness, route transmission reliability, and the success rate of network communication in highly dynamic node environments.